1989
DOI: 10.1021/bi00436a025
|View full text |Cite
|
Sign up to set email alerts
|

Laser temperature-jump, spectroscopic, and thermodynamic study of salt effects on duplex formation by dGCATGC

Abstract: Salt effects on duplex formation by dGCATGC have been studied with spectroscopic, thermodynamic, and kinetic methods. Circular dichroism spectra indicate different salt conditions have little effect on the structures of the duplex and single strand. NMR chemical shifts indicate the structure of the duplex in 1 M NaCl is similar to that of the B-form determined previously in 0.5 M KCl [Nilges, M., Clore, G. M., Gronenborn, A. M., Brunger, A. T., Karplus, M., & Nilsson, L. (1987) Biochemistry 26, 3718-3733]. Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
180
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(217 citation statements)
references
References 51 publications
36
180
0
Order By: Relevance
“…Optical melting experiments of RNA oligomers are usually performed in 1+0 M monovalent ion (Na ϩ ) conditions to compensate for the absence of divalent ions+ To investigate the role of Mg 2ϩ ions on the stability of RNA oligomers, the concentration of monovalent ions in these optical melting experiments was set to a more physiological concentration of 0+1 M NaCl (Table 1)+ In all cases, there was good agreement between the thermodynamic values derived from the T M Ϫ1 versus log C t plots and the melt curves (see Materials and Methods)+ As expected, all of the oligomers were more stable in 1+0 M NaCl than in 0+1 M NaCl melt buffer (Table 1); the hexamer duplex has a higher melting temperature by 7+7 8C, the octamer duplex by 10+5 8C and the 14mer by 13+4 8C+ The changes in melting temperature for the RNA oligomers are summarized in Table 2+ The differences in melting temperatures between 1+0 M and 0+1 M melt buffer were 8-10 8C for oligomers with tandem GA base pairs and about 9-10 8C for oligomer duplexes with tandem GU base pairs+ Thus, both the GA and GU sequences present changes in melting temperatures similar to those of duplexes of comparable length+ The introduction of non-WatsonCrick pairs within a duplex seems to have minimal effects on the relative stabilities of the oligomers in melt buffer containing only monovalent ions+ The largest oligomer investigated, containing the eubacterial loop E motif flanked by Watson-Crick pairs (13 nt), had the largest change in melting temperature (almost 23 8C)+ The other oligomers with the loop E motifs (loop E hairpin and eukaryotic) have only modest temperature changes: 8-9 8C+ The three duplex sequences were then melted in 0+1 M NaCl melt buffer with a series of magnesium ion concentrations up to 50 mM+ The thermodynamics for duplex formation by the oligomers in 50 mM MgCl 2 , 0+1 M NaCl melt buffer is presented in Table 1; all of the duplexes are more stable in buffer containing Mg 2ϩ ion+ The melting temperature of hexamer duplex increases by 12+1 8C, the octamer duplex increases by 11+2 8C, and the 14mer duplex increases by 11+0 8C+ As opposed to the stability increases in monovalent ions, the stability increases observed with magnesium ion are inversely related to the size of the oligomer (Table 2)+ 308 M.J. Serra et al Except for the 14 mer, the melting temperature of the duplex sequences in the 50 mM Mg 2ϩ buffer are larger than those observed in the 1+0 M NaCl melt buffer despite the fact that the magnesium buffer has only half the ionic strength of the 1+0 M NaCl buffer+ In general, the van't Hoff enthalpy increases slightly with the addition of magnesium ion+ However, the 14mer actually presents a slight decrease in the van't Hoff enthalpy in the 50 mM magnesium ion melt buffer relative to the 0+1 M NaCl melt buffer without magnesium ion (Table 1)+ Figures 1A,B display the changes in melting temperature of the duplexes with increasing magnesium ion concentration+ The results seen here for the RNA oligomers are similar to those observed previously for a DNA duplex (59d(GCATGC) 2; Williams et al+, 1989) indicating that similar interactions occur with magnesium ions and both DNA and RNA oligomers+ The effect of magnesium ion on the thermal stability of the oligomers can be interpreted using either of two simple models (Laing e...…”
Section: Resultssupporting
confidence: 78%
“…Optical melting experiments of RNA oligomers are usually performed in 1+0 M monovalent ion (Na ϩ ) conditions to compensate for the absence of divalent ions+ To investigate the role of Mg 2ϩ ions on the stability of RNA oligomers, the concentration of monovalent ions in these optical melting experiments was set to a more physiological concentration of 0+1 M NaCl (Table 1)+ In all cases, there was good agreement between the thermodynamic values derived from the T M Ϫ1 versus log C t plots and the melt curves (see Materials and Methods)+ As expected, all of the oligomers were more stable in 1+0 M NaCl than in 0+1 M NaCl melt buffer (Table 1); the hexamer duplex has a higher melting temperature by 7+7 8C, the octamer duplex by 10+5 8C and the 14mer by 13+4 8C+ The changes in melting temperature for the RNA oligomers are summarized in Table 2+ The differences in melting temperatures between 1+0 M and 0+1 M melt buffer were 8-10 8C for oligomers with tandem GA base pairs and about 9-10 8C for oligomer duplexes with tandem GU base pairs+ Thus, both the GA and GU sequences present changes in melting temperatures similar to those of duplexes of comparable length+ The introduction of non-WatsonCrick pairs within a duplex seems to have minimal effects on the relative stabilities of the oligomers in melt buffer containing only monovalent ions+ The largest oligomer investigated, containing the eubacterial loop E motif flanked by Watson-Crick pairs (13 nt), had the largest change in melting temperature (almost 23 8C)+ The other oligomers with the loop E motifs (loop E hairpin and eukaryotic) have only modest temperature changes: 8-9 8C+ The three duplex sequences were then melted in 0+1 M NaCl melt buffer with a series of magnesium ion concentrations up to 50 mM+ The thermodynamics for duplex formation by the oligomers in 50 mM MgCl 2 , 0+1 M NaCl melt buffer is presented in Table 1; all of the duplexes are more stable in buffer containing Mg 2ϩ ion+ The melting temperature of hexamer duplex increases by 12+1 8C, the octamer duplex increases by 11+2 8C, and the 14mer duplex increases by 11+0 8C+ As opposed to the stability increases in monovalent ions, the stability increases observed with magnesium ion are inversely related to the size of the oligomer (Table 2)+ 308 M.J. Serra et al Except for the 14 mer, the melting temperature of the duplex sequences in the 50 mM Mg 2ϩ buffer are larger than those observed in the 1+0 M NaCl melt buffer despite the fact that the magnesium buffer has only half the ionic strength of the 1+0 M NaCl buffer+ In general, the van't Hoff enthalpy increases slightly with the addition of magnesium ion+ However, the 14mer actually presents a slight decrease in the van't Hoff enthalpy in the 50 mM magnesium ion melt buffer relative to the 0+1 M NaCl melt buffer without magnesium ion (Table 1)+ Figures 1A,B display the changes in melting temperature of the duplexes with increasing magnesium ion concentration+ The results seen here for the RNA oligomers are similar to those observed previously for a DNA duplex (59d(GCATGC) 2; Williams et al+, 1989) indicating that similar interactions occur with magnesium ions and both DNA and RNA oligomers+ The effect of magnesium ion on the thermal stability of the oligomers can be interpreted using either of two simple models (Laing e...…”
Section: Resultssupporting
confidence: 78%
“…For example, a differentially reduced electrostatic repulsion of ssDNA enhances the association rate of hybridization (35). Divalent ions show this effect as confirmed by in vitro measurements demonstrating a strong acceleration with increasing MgCl 2 concentration for both probes (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…. k 2 and the first regime holds true (Fig+ 5, triangles)+ If cleavage is not affected by the chase, k Ϫ1 , , k 2 and the second regime fits (Fig+ 5, squares)+ Certain hammerheads have a rate of substrate dissociation on the order of the rate of chemistry, k Ϫ1 Х k 2 so that cleavage is seen during the chase period (Fig+ 5, diamonds)+ In this relatively unusual case, k Ϫ1 can be determined directly from the chase experiment by one of two methods (Fedor & Uhlenbeck, 1992)+ For some hammerhead sequences, the kinetic regime can be changed by altering the pH of the reaction and thereby changing k 2 (Werner & Uhlenbeck, 1995;Clouet-d'Orval & Uhlenbeck, 1996)+ Because k Ϫ1 is not expected to depend on pH, changing the pH effectively alters the relative values of the two rate constants and potentially creates regime-one conditions+ Determining the kinetic regime for a hammerhead by the pulse-chase experiment defines the strategy to obtain k 1 and k Ϫ1 , the elemental rate constants for the binding step+ For hammerheads in the first regime, k 1 and k Ϫ1 cannot be determined directly, although K d ϭ k Ϫ1 /k 1 is easily obtained (see next section)+ For hammerheads in the second regime, k 1 can be obtained by measuring the rate of cleavage at subsaturating ribozyme concentration where binding is rate-limiting+ Under these conditions, k obs ϭ k 1 [R]+ The value of k 1 has only been measured for a limited number of hammerheads, but a value between 10 7 and 10 8 M Ϫ1 min Ϫ1 is usually obtained (Fedor & Uhlenbeck, 1992;Hertel et al+, 1994)+ This value is similar to k 1 values reported for simple RNA duplexes in high concentrations of monovalent cation (Pörschke & Eigen, 1971;Pörschke et al+, 1973;Nelson & Tinoco, 1982)+ However, k 1 values of DNA helices in buffers containing MgCl 2 are often faster (Williams et al+, 1989), suggesting that faster hammerhead association rates may be possible+…”
Section: Two Kinetic Regimesmentioning
confidence: 69%